Respuesta a la aplicación de las cepas de Trichoderma harzianum y Micorriza (Glomus intraradices) en dos tipos de sustratos en la propagación de patrones de rosa en la zona de San Antonio de Ibarra, provincia de Imbabura - Lárraga Vinueza, Jorge Mario (2014)
This research was conducted in the field of Chorlavi of the parish of San Antonio de Ibarra, Imbabura province, in order to study the response to the application of Trichoderma harzianum strains and mycorrhizal (Glomus intraradices) on two types of substrates in the spread patterns rose (Rosa sp.) Brian Nathal variety. The treatments were prepared substrates between black earth (60%) + humus (20%) and gravel (20%), using Trichoderma harzianum in doses of 90 cc / und; black earth (60%) + humus (20%) and gravel (20%) with application of mycorrhiza (Glomus intraradices) in doses of 90 cc / und; black earth (60%), humus (20%) and gravel (20%) using Trichoderma harzianum in doses of 90 cc / und and mycorrhizal (Glomus intraradices) in doses of 90 cc / und; Coir (50%) and humus (50%) applied in doses of Trichoderma harzianum 90 cc / und; Coconut fiber (50%) and humus (50%) using mycorrhizal (Glomus intraradices) in doses of 90 cc / und; Coir (50%) and humus (50%) applied in doses of Trichoderma harzianum 90 cc / und and mycorrhizal (Glomus intraradices) in doses of 90 cc / und; Black Earth (60%), humus (20%) and gravel (20%) without product and coconut fiber (50%) and humus (50%) without product. The design was used for research at random (DCA) with eight treatments and three repetitions. The variables were evaluated: percentage of seizure at 20 ddt, shoot length (tirasabia) 30; 45 and 55 ddt, root length at 55 ddt, tirasabia number of sheets 30; 45 and 55 ddt, fresh root weight at 55 ddt, fresh weight of foliage leaves at 55 ddt, marketing days and determining the presence of Trichoderma harzianum and mycorrhiza (Glomus intraradices) substrate and result in patterns pink. All variables applied were subjected to ANOVA using Tukey's test at 5%.